Response: The Problem of Shifting Scientific Paradigms: On Avoiding Premature Closure of Questions in Science and Religion - McGrath, Alister E. (Heythrop journal, 2025)
This paper responds to the papers gathered together in this volume on biocultural evolution by focusing particularly on two of them that raise questions of particular interest. Victoria Lorrimar's critique of purely rationalist accounts of both the scientific enterprise in general, and human quest for truth and meaning on the other. It develops Lorrimar's argument that the human sense-making apparatus is complex and dispersed, enfolding what are generally described as ‘reason’, ‘imagination’, and ‘intuition’. Michael Burdett's reflection on evolutionary theory indirectly raises a neglected problem that clearly requires further attention—the question of follow-through on theological assessments of developments in the natural sciences, particularly evolutionary biology. Discussion of some questions in the field of science and religion often tends to be ‘frozen’ at a specific historical point, and subsequently discussed without reference to downstream reflections. This point is illustrated by reflecting on the 2013 collaborative project between the theologian Sarah Coakley and the evolutionary biologist Martin Nowak, which emphasised the role of cooperation within the evolutionary framework. It is important to ensure ongoing engagement with such questions, rather than leaving them suspended in an incomplete state of resolution, or ‘freezing’ the provisional answers given decades ago, as if these were definitive. [Correction added on 12 April 2025: Abstract section have been included in this version.]